2010
DOI: 10.1521/aeap.2010.22.5.466
|View full text |Cite
|
Sign up to set email alerts
|

Central American Sex Workers' Introduction of the Female Condom to Different Types of Sexual Partners

Abstract: Formative research was conducted in El Salvador and Nicaragua to inform promotion of female condoms to sex workers. Two rounds of focus groups with sex workers were conducted, with female condom training and supplies provided. Structured interviews with sex workers and direct observations of health educators were conducted. One third of sex acts were protected with female condoms in the previous 7 days. Women recommended nonpaying partners as "first try" partners but most frequently reported trying female cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…Some studies reported that stigmatized notions of the FC impeded initial use and were widely expressed by men, women, and health care providers, 52 , 54 , 73 , 78 , 79 linking the device with infidelity and commercial sex work, even when marketed as a contraceptive for stable couples. 54 , 61 , 66 , 68 , 78 – 81 For example, a quarter of female participants in a Kenyan study felt that using or carrying an FC was synonymous with unfaithfulness. 61 Researchers in Zimbabwe commented that “just like the male condom, the [FC] was seen as a threat to intimacy and commitment, in that requesting them would introduce an element of distrust and suspicion of infidelity and promiscuity”.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies reported that stigmatized notions of the FC impeded initial use and were widely expressed by men, women, and health care providers, 52 , 54 , 73 , 78 , 79 linking the device with infidelity and commercial sex work, even when marketed as a contraceptive for stable couples. 54 , 61 , 66 , 68 , 78 – 81 For example, a quarter of female participants in a Kenyan study felt that using or carrying an FC was synonymous with unfaithfulness. 61 Researchers in Zimbabwe commented that “just like the male condom, the [FC] was seen as a threat to intimacy and commitment, in that requesting them would introduce an element of distrust and suspicion of infidelity and promiscuity”.…”
Section: Resultsmentioning
confidence: 99%
“… 48 FSWs in Brazil and El Salvador reported using FCs more often with regular clients than with new/occasional clients or boyfriends. 67 , 68 Conversely, despite both sexes generally perceiving dual protection as an advantage, women in Swaziland, Zimbabwe, Cote d’Ivoire, and India reported discomfort discussing disease prevention with long-term partners. 69 , 70 , 119 , 120…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since FC was first introduced, studies of acceptability and usage have been widely conducted among sex workers (Witte, El-Bassel, Wada, Gray, & Wallace, 1999; Jivasak-Apimas et al, 2001; Cheng et al, 2002; Zachariah, Harries, Buhendwa, Spielman, Chantulo, & Bakali, 2003; Thomsen et al, 2006; Hoke et al, 2007; Lara, Grossman, Munoz, Rosario, Gomez, & Garcia, 2009; Mack, Grey, Amsterdam, Matta, & Williamson, 2010; Liao et al, 2011a; Liao et al, 2011b), couples (Musaba, Morrison, Sunkutu, & Wong, 1998; Lawson et al, 2003; Smita et al, 2005; Lameiras Fernandez, Failde Garrido, Castro, Nunez Mangana, Carrera Fernandez, & Foltz, 2008), patients from clinics (Artz et al, 2000; Hoffman, Exner, Leu, Ehrhardt, & Stein, 2003; Kulczycki, Kim, Duerr, Jamieson, & Macaluso, 2004), and volunteers (Barbosa, Kalckmann, Berquo, & Stein, 2007). Despite numerous studies demonstrating high acceptability of FC among various populations, its use remains low and a large proportion of women who initially tried it did not sustain its use (Hoffman et al, 2004; Gallo, Kilbourne-Brook, & Coffey, 2012).…”
Section: Introductionmentioning
confidence: 99%